PAA Africa's contributions to the consolidation of PRONAE in Mozambique - Carolina Milhorance de Castro (International Policy Centre for Inclusive Growth (IPC-IG), 2018)
The public purchasing of food from family farming has the potential to ensure that vulnerable populations have access to locally produced food, income generation, strategic stockpiling and food assistance, by providing food to schools, restaurants, hospitals and other public institutions. This strategy combines food assistance with measures to support production, and focuses on strengthening the social and institutional conditions in the country. A structured demand for small producers affords greater security to the production planning process and to the organisation and respective remuneration of producers. These initiatives have demonstrated the capacity of family farmers and their associations to bring quality products to market, thus contributing to rural development. [...]
Keywords: 330; PAA; Africa; contributions; consolidation; PRONAE; Mozambique